The roles of the game : the influence of news consumption patterns on the role conceptions of journalism students - Tandoc, Edson C. (2014)
This study is based on a survey of 364 undergraduate journalism students and looks at how news consumption patterns influence the journalistic role conceptions that students hold. This study finds that students rated the interpreter role as most important. Students who prioritized the interpreter role also tend to get their news from online sources and social media. The implications of these findings on college instruction are also discussed.